Analysis of the Concept of Self-Awareness in Sufism and its Implications in the Guidance Counseling Process - Amida, Iis Amanah; Nugraha, Bambang Kurnia (Formosa Journal of Sustainable Research, 2024)
This research aims to analyze the concept of self-awareness in Sufism and identify its implications in the counseling guidance process. The research method uses a qualitative approach with content analysis to explore Sufism texts related to self-awareness. The implications of the concept of self-awareness in Sufism for the counseling guidance process are detailed, including the development of counseling interventions that are more oriented towards spiritual values, individual empowerment in absorbing Sufism values, and the use of Sufism techniques in improving psychological well-being. This research makes an important contribution in enriching the counseling guidance literature with a Sufism perspective, offering a deeper understanding of the concept of self-awareness which includes a spiritual dimension. The practical implications of this research can be used as a basis for developing a more holistic and sustainable counseling guidance program, combining Sufism values with modern counseling principles